Effect of carbon addition on the microstructure and mechanical behavior of near equiatomic NiTi alloy wire. (January 2023) - Zhao, Yang; Yu, Zunyue; Wang, Qianyu; Zhang, Beibei; Ren, Xuepeng; Zhao, Wenru; Ren, Shubin; Qu, Xuanhui
Graphical abstract: Highlights: NiTiC alloy wires were prepared by accurately adjusting the C content. NiTi alloy with 0.03 wt% C exhibits excellent tensile strength and tensile fatigue life. Stacking faults in different directions in eutectic TiC form Lomer-Cottrell locks. Stacking faults occur in grain boundaries of eutectic TiC in contact with matrix. Eutectic TiC hinders the movement of adjacent grain boundaries and dislocations. Abstract: According to the phase diagram, 0.03 wt% (C0.03) and 0.05 wt% (C0.05) carbon were added to Ni50.2Ti49.8 alloy, and the alloy wires with a diameter of 1.2 mm were prepared by vacuum induction melting and drawing. The results show that during melting and solidification, C combines with Ti in C0.03 and C0.05 to form eutectic TiC and primary TiC, respectively. Compared with the NiTi alloy wire without C, the tensile fatigue life (22866 cycles under 700 MPa tensile stress) and tensile strength (1536 MPa) of the alloy were increased by 39 % and 22 % respectively when 0.03 wt% C was added. With the further increase of C content to 0.05 wt%, the two properties began to deteriorate. This is mainly related to the changes of matrix phase composition, second phase morphology and internal microstructure caused by the addition of different amounts of C. The research results show that on the premise of following the requirements for C content (C ≤ 0.04 wt%) in the international standard ASTM F2063-18 for medical NiTi alloy composition, adding a certain amount of C (such as 0.03 wt%) to NiTi alloy is beneficial to improving the tensile strength and tensile fatigue life of wire.